The Effect of Preoperative Video Based Pain Training on Postoperative Pain and Analgesic Use in Patients Undergoing Total Knee Arthroplasty: A Non-randomized Control Group Intervention Study - GÜNDÜZ, CEYDA SU (SAGE PUBLICATIONS INC, 2021)
This non-randomized control group intervention study was conducted to determine the effect of preoperative video based pain training on postoperative pain and analgesic use in patients undergoing total knee arthroplasty. During the study, the patients in the control (n = 40) received routine care and the patients in the intervention group (n = 40) received video based pain training. It was determined that the mean postoperative pain scores of the intervention group were significantly lower and their pain management was better compared to the control group (p < .05). The intervention group was found to use significantly less paracetamol on operation day compared to the control group (p < .05). The intervention group was determined to benefit from non-pharmacological methods more than the control group did (p < .05). Providing video based pain training to patients undergoing total knee arthroplasty is recommended since it reduces postoperative pain levels and increases the use of non-pharmacological pain control methods.
Keywords: audiovisual aids; pain management; patient education; perioperative nursing; total knee arthroplasty